Analisis Faktor-Faktor yang Mempengaruhi Minat Konsumen dalam Menggunakan Aplikasi Emaal pada Swalayan Basmalah Cabang Ngempit Kraton - Anisak Anisak; Saiful Bakhri (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2025)
This study examines the factors influencing consumer interest in using the Emaal application at Basmalah Supermarket, Ngempit branch. The research employs a descriptive qualitative approach, involving interviews with active users of the Emaal application. The findings reveal that key drivers include perceived usefulness, ease of use, transaction convenience, and transaction security. Consumers value features such as cashless payments, loyalty rewards, and the ability to track transaction histories. However, barriers such as limited consumer awareness, slow application response times, and competition with conventional payment methods also impact adoption. The study underscores the need for strategic marketing, consumer education, and technological optimization to enhance user adoption rates. These insights provide practical guidance for Basmalah in tailoring its digital marketing strategies to the needs of the Ngempit demographic.